USA 2012 after the middle-class revolution - Dolbeare, Kenneth M. 1930-; Hubbell, Janette Kay (Chatham House Publ., 1996)
He uses as his starting point the New Declaration of Independence of the Fourth of July, 2000, and explores first how it came about and then how its commitments were steadily achieved in the following years through sustained middle-class mobilization, electronic communication, a series of practical and populist constitutional changes, and a prosperity-restoring, middle class-oriented economic nationalist policy program